HUBUNGAN USIA IBU SAAT HAMIL, USIA KEHAMILAN DAN BERAT BADAN LAHIR DENGAN KEJADIAN HIPOSPADIA DI RSUP DR. M. DJAMIL PADANG - Sd. Ahmad Isa; Siti Nurhajjah; Alvarino Alvarino; Nelmi Silvia (SINERGI : Jurnal Riset Ilmiah, 2026)
Hypospadias has been shown to be influenced by maternal age, with older mothers, particularly those over 35 years old, having an increased risk of giving birth to male infants with this condition. Studies indicate that advanced maternal age is associated with a higher likelihood of hypospadias compared to younger mothers. Additionally, low birth weight is another significant factor, as infants with lower birth weights tend to have a higher incidence of hypospadias. This research aims to investigate the relationship between maternal age during pregnancy, gestational age, and birth weight with the occurrence of hypospadias. This study was an observational analytic study with a case-control design conducted at Dr. M. Djamil Hospital Padang. The sample of this study amounted to 80 hypospadias patients diagnosed in the period January 2019 to December 2023 and 80 control patients taken from patients who sought treatment at the pediatric polyclinic in the period January to December 2022. Data were analyzed using the chi-square test, if a p value <0.05 was obtained, there was a relationship between the dependent and independent variables.This study was found that there was an association between maternal age during pregnancy (p-value = 0.037), gestational age (p-value = 0.018) and birth weight (p-value = 0.002) with the incidence of hypospadias. The conclusion of this study is that there is a relationship between maternal age at pragnancy, gestational age, birth weight and the incidence of hypospadias at Dr. M. Djamil Padang Hospital. Suggestions for further research are expected to explore other risk factors that can cause hypospadias.